TANGGUNG JAWAB NOTARIS ATAS PELANGGARAN TERHADAP PENANDATANGANAN AKTA YANG TIDAK DILAKUKAN DIHADAPAN NOTARIS - Lutfia, Lutfia; Bangun, Budi Hemawan; Alhadiansyah, Alhadiansyah (Faculty Of Law, Universitas Tanjungpura, 2022)
Abstract The deed made by or before a Notary is an authentic deed, the party who denies the truth of an authentic deed must be able to prove otherwise. It is necessary to review further regarding the practice of signing a deed that is not done before a notary and the responsibility of a notary who does not sign a deed that is done in his presence. It is intended to answer the problem, how is the strength of proof of a notary deed whose signing is not carried out before a notary but is carried out before a notary employee, how is the notary's legal responsibility for a deed he made that was not signed before a notary but was carried out before a notary employee and how the efforts were made to prevent acts against the law carried out by a notary in making a deed. Conclusion in the first study, the strength of proof of a notary deeds whose signing is not done before a notary but is carried out in front of a notary employee, then the deed is not authentic and has no legal force. Based on the provisions of Law no. 2 of 2014 jo. UU no. 30 of 2004 concerning the Position of a Notary, Article 16 Paragraph (1) letter m states that: